Growth and Yield of Three Varieties of True Shallot Seed with Application of Plant Growth Regulators and Boron Formulations - Sulandjari Sulandjari; Eddy Triharyanto; Djoko Purnomo; Endang Setia Muliawati; Hasbiya Rizqy Sabrina Sobari Putri (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Optimization of shallot production can use True Shallot Seed (TSS) and Plant Growth Regulator (PGR) + Boron formulation. The purpose of the study was to identify superior varieties that respond to the concentration of PGR + Boron formulation and can provide the best results. The research location was at 7°32’30” N and 110°48’32” E, from October 2023 to February 2024. A randomized complete block design factorial with two treatment factors was used, each repeated three times. The first is the type of variety (Lokananta, Maserati, and Sanren), the second is the type of PGR + Boron formulation, the composition of GA3+BAP+Boron (ppm:ppm:kg.ha-1) with four levels, that were 0:0:0, 50:25:2, 100:50:2, and 150:75:2. Conclusion, The Maserati variety of shallots from TSS with a PGR formulation of 100 ppm GA3 + 50 ppm BAP + 2 kg.ha-1 Boron produces better growth and yields than the Lokananta and Sanren varieties.